2011
DOI: 10.1093/hmg/ddr365
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genomic basis of pharmacoresistance in epilepsy: an integrative analysis of large-scale gene expression profiling studies on brain tissue from epilepsy surgery

Abstract: Some patients with pharmacoresistant epilepsy undergo therapeutic resection of the epileptic focus. At least 12 large-scale microarray studies on brain tissue from epilepsy surgery have been published over the last 10 years, but they have failed to make a significant impact upon our understanding of pharmacoresistance, because (1) doubts have been raised about their reproducibility, (2) only a small number of the gene expression changes found in each microarray study have been independently validated and (3) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 80 publications
0
39
0
1
Order By: Relevance
“…This could be explained by the fact that most AEDs do not seem to be substrates of ABCB1 [199,200] and that the impact of SNPs on ABCB1 expression in the bloodbrain barrier is only modest [201,202]. The observed overexpression of ABCB1 in epileptic brain tissue could, therefore, be just an epiphenomenon [203], suggesting the involvement of other genes [202,204,205].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…This could be explained by the fact that most AEDs do not seem to be substrates of ABCB1 [199,200] and that the impact of SNPs on ABCB1 expression in the bloodbrain barrier is only modest [201,202]. The observed overexpression of ABCB1 in epileptic brain tissue could, therefore, be just an epiphenomenon [203], suggesting the involvement of other genes [202,204,205].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Meta-analysis methods that integrate the results of separate genomic assessments are now being used to allow the identification of cellular components, biological processes, molecular functions, pathways, networks, and individual genes in diseases such as epilepsy. 63 This strategy could be used in psoriasis, in which sufficient comparable genomic data exist.…”
Section: Recommendations To Researchers and Journalsmentioning
confidence: 99%
“…These authors showed that for some epilepsy phenotypes it is becoming possible to predict the most efficacious antiepileptic drugs for patients based on their genetic makeup (Yamada et al, 2013;Sugawara et al, 2013). In a similar way pharmacoresistance can be determined by genetic studies (Mirza et al, 2011;Lachos et al, 2011). Thus, the development of individualized medicine is expected to greatly improve the management of epilepsy patients .…”
Section: Genetic Testing In the Epilepsiesmentioning
confidence: 99%